First Case Mild Symptoms COVID-19 in Rural Central Java Area: Case Report of an Indonesian Patient - Limijadi, Edward Kurnia Setiawan; Ramadhani, Inge Cahya; Hartutiningtyas, Dian Tunjungsari; Brajadenta, Gara Samara (Open Access Macedonian Journal of Medical Sciences, 2023)
Background: SARS-CoV-2 virus infection is a pandemic that began to emerge in December 2019 in various countries with high death rates of 4-9% until now. In March 2020, Indonesia found its first case where the condition of the infection kept spreading to various regions in Indonesia. Different regional conditions in Indonesia make it difficult to manage this virus infection. The capability of the regional hospitals to detect this virus infection with their facilities and infrastructure is required. Case presentation: A 17-year-old man came to the Ajibarang Regional Hospital with complaints of coughs and colds felt for four days and fever for two days. Physical examination found a good general condition, moderate pain, the temperature of 38.8°C, pharyngeal hyperemia, and minimal lung crackles sound. Laboratory tests showed normal leukocytes, platelet, and hemoglobin levels. Chest radiograph was suggestive of bronchitis. The patient was hospitalized for approximately four days until the fever resolved and was discharged. Five days after the patient was discharged from the hospital, the results of the viral load examination using RT-PCR confirmed positive for COVID-19. Conclusion: This case showed unusual conditions of a mild clinical COVID-19 infection, laboratory results that did not support viral infections, as well as radiology examination of only bronchitis. The viral load test was found to be positive. Therefore, the diagnosis of the COVID-19 infection requires a comprehensive interpretation of complete history taking, clinical examination, laboratory and radiology examinations for clinicians working with limited hospital facilities and infrastructures.